Legal Norms Contract With The Constitutional Rights Of Citizens As Guaranteed In The 1945 Constitution In The Establishment Of The Work Copyright Law - Benyamin Tungga; Yossie Maria Yulianty Jacob; Susi Ratnawati (Syntax Corporation, 2022)
From the outset, the Job Creation Bill was aimed at strengthening large-scale companies and investors. It is unfortunate because the formulation process was closed, rushed, including ignoring the principle of prudence in formulating changes to hundreds of articles of various laws without taking into account the social, economic, political and cultural impacts that will inevitably arise. Its formulation which involves business elites and pro-capital academics is also truly unfortunate. One of the legal issues highlighted is Law No. 32 of 2009 concerning Environmental Protection and Management (PPLH), especially related to Amdal (Analysis of Environmental Impacts). Where there is a legal issue that states this AMDAL is deleted. The purpose of this study is to examine the legal norms that contradict the constitutional rights of citizens as guaranteed in the 1945 Constitution in the formation of the Job Creation Law. The method used in this research is a qualitative method. The author uses a qualitative descriptive method in this research, as well as a literature study. The research in this paper is in the field of juridical-normative law. The results of the study Based on the various difficulties in the formation of the law, it seems that the Indonesian people have long felt as a developing country. The difficulties in the formation of this law are now more felt by the Indonesian people, who are currently facing various social problems based on multi-dimensional structural and cultural problems. In fact, the formation of this law now and in the future will continue to increase in response to the demands of the community along with the increasing complexity of the development and conditions of society. This can be seen from the demonstration against the Ratification of the Omnibus Law on Job Creation.